Differences in Power Acquisition Between Only and Non-only Children: The Effects of Cooperative Orientation, Competitive Orientation, and Dependency on Parents - Rong, Yan; Han, Yulan; Dong, Linping; Bi, Huijuan (Frontiers in Psychology, 2022)
Drawing upon a developmental perspective, we investigated the differences in power acquisition (i.e., rank at work and leader role occupancy in university) between only and non-only children as well as the mediating role of cooperative and competitive orientations and the moderating role of dependency on parents. To test our hypotheses, we conducted two field studies in 155 part-time Master of Business Administration (MBA) students (Study 1) and 375 senior students (Study 2). Results showed that: (1) non-only children were more likely to achieve higher rank at work than only children; (2) only children were less likely than non-only children to acquire power in organizations because they scored lower in cooperative orientation; however, the mediating effect of competitive orientation was not significant; (3) the difference in cooperative orientation between only and non-only children was smaller when dependency on parents was high, whereas it became larger when dependency on parents was low. Our research contributes to the understanding of how family structure influences individual power acquisition.